2010
DOI: 10.1111/j.1365-2621.2010.02349.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different precooking methods on chemical composition and lipid damage of silver carp (Hypophthalmichthys molitrix) muscle

Abstract: The influence of three precooking methods (steaming, oven-baking and microwave-cooking) on the chemical composition and lipid quality of silver carp fillets was evaluated. The changes in protein, fat and moisture were found to be significant for all the treatments (P £ 0.05). The iron content in the samples subjected to steam-cooking increased; however, the other precooking methods did not change the mineral contents (P ‡ 0.05). The free fatty acid content of the fillets did not change by the different precook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…There was no difference in PI value of the cooked sample when compared to the raw fish. Some previous research on cooking Naseri et al, 2010) has shown that the polyunsaturated fatty acids proportion in total lipids did not diminish as a result of precooking processes. A significant decrease Results are means ± standard deviation.…”
Section: Polyene Indexmentioning
confidence: 97%
“…There was no difference in PI value of the cooked sample when compared to the raw fish. Some previous research on cooking Naseri et al, 2010) has shown that the polyunsaturated fatty acids proportion in total lipids did not diminish as a result of precooking processes. A significant decrease Results are means ± standard deviation.…”
Section: Polyene Indexmentioning
confidence: 97%
“…Some authors investigated cooking methods without adding any oil or fat and only one reference was found to the investigation of deep fat frying of whole carp fillets. (Tothmarkus & Sasskiss 1993;De Castro et al 2007;Naseri et al 2010). A very recent publication described for the first time shallow fat frying of silver carp with olive, sunflower, and canola oils (Rahimabadi & Dad 2012).…”
mentioning
confidence: 99%
“…Consumption of ω‐3 fatty acids is related to benefits in cardiovascular health due to their anti‐inflammatory nature. The greatest concentrations of eicosapentaenoic acid (EPA, 20:5, ω‐3) and decosahexaenoic acid (DHA, 22:6, ω‐3) were identified in the 40 °C protein powder at 8.31 and 9.03%, respectively, which are greater than reported concentrations of EPA (1.78%) and DHA (2.25%) in fresh silver carp fillets (Naseri, Rezaei, Moieni, Hosseni, & Eskandari, ). The EPA and DHA concentrations for silver carp fillets were expected to be similar to that of the initial fish homogenate used in the current study; however, they were up to 3 times lower (Naseri et al., ).…”
Section: Resultsmentioning
confidence: 81%